IDENTIFICATION OF A SUITABLE CROP SEQUENCE MODULE FOR INTEGRATED FARMING SYSTEM OF TELANGANA (INDIA) UNDER IRRIGATED SITUATION (Applied Biological Research, 2023)
A field experiment was conducted for two years (2017-2019) at the College  Farm, AICRP on Integrated Farming Systems unit, PJTSAU, Hyderabad  (India) to identify the profitable cropping system module for different  integrated farming systems under irrigated situation in sandy loam soils of  Southern Telangana zone, Telangana (India). Among the ten cropping  systems evaluated, sweet corn-vegetable (tomato) system was found more  remunerative with B:C ratio 3.54, followed by okra-marigold-beetroot  system with B:C ratio of 2.92. Among the ecological cropping systems for  improving the soil health, Bt cotton + green gram (1:3)-groundnut  cropping system gave significantly higher rice grain equivalent yield  (13,687 kg ha-1), however the net returns were high (₹ 1,37,259 ha-1) in  pigeon pea + green gram (1:7)-sesame cropping system. Out of the two  systems tested to meet the household nutritional security, pigeon pea +  maize (1:3)-groundnut system gave higher rice grain equivalent yield  (13,772 kg ha-1) with higher net returns (₹ 1,35,959 ha-1). Within the two  fodder crops/cropping systems, fodder maize-lucerne system showed  higher B:C ratio (1.64). Fodder systems were more exhaustive than all  other cropping systems. However, within two years of experimentation the  changes in physicochemical properties and soil fertility status were not  significantly affected.
Keywords: Cropping systems; economics; rice grain equivalent yield (RGEY); system productivity; system profitability